Do central vestibular findings predict abnormal findings on magnetic resonance imaging?. Issue 7 (14th June 2019) - Mankekar, G; Jeha, G; Erbele, I; Klumpp, M; Sevy, A; Mehta, R; Son, L; Arriaga, M A
Abstract: Objective: To determine whether central findings from vestibular tests predict abnormal findings on magnetic resonance imaging. Method: This study was a retrospective case series at a tertiary referral centre. The main outcome measure of this diagnostic intervention study was the positive predictive value of central vestibular findings in relation to magnetic resonance imaging abnormalities. Results: Central vestibular findings had a 50.9 per cent positive predictive value for magnetic resonance imaging abnormalities across all age groups although they varied according to age group. Optokinetic nystagmus ( p < 0.05) and abnormal findings on videonystagmography tests ( p < 0.05) were the main predictors of magnetic resonance imaging abnormalities. White matter lesions constituted the bulk of the central lesions on magnetic resonance imaging followed by cortical and cerebellar atrophy. Conclusion: Central vestibular findings had a 50.9 per cent positive predictive value for magnetic resonance imaging abnormalities across all age groups. Magnetic resonance imaging is medically justified to further evaluate patients with central findings on vestibular studies. Therefore, it is reasonable to request magnetic resonance imaging in these patients.